The effects of brand strategy and design innovation on the brand performance of the Malaysian furniture firms / Puteri Fadzline Muhamad Tamyez - Muhamad Tamyez, Puteri Fadzline (Institute of Graduate Studies, UiTM, 2015)
Brand strategy and design innovation is frequently discussed as key sources of competitive advantage and subsequent brand performance, particularly in the context of SMEs and large sized firms. One of the sectors that are affected by the growth of branding and design innovation is the furniture manufacturing sector. However, there is a concern of whether the manufacturers are fully equipped with branding strategy and design innovation. This ambiguity comes largely from determinants of brand performance in the SME context that have received only limited research attention. This research addresses this issue. Therefore, the main objective of this study is to examine the effects of brand strategy and design innovation on the brand performance of the Malaysian furniture firms. More specifically, this research empirically examines (1) The influence of brand barriers on brand orientation (2) The influence of brand orientation towards brand distinctiveness (3) The relationship between brand orientation and brand performance (4) The relationship between brand distinctiveness and brand performance (5) The influence of brand distinctiveness on design innovation (6) The relationship between design innovation and its dimensions (7) The effect of design innovation on brand performance (8) brand distinctiveness as a mediator between brand orientation and brand performance (9) design innovation as a mediator between brand distinctiveness and brand performance, along with twelve hypotheses…